2019
DOI: 10.1093/jhps/hnz020
|View full text |Cite
|
Sign up to set email alerts
|

High relative reliability and responsiveness of the forgotten joint score-12 in patients with femoroacetabular impingement undergoing hip arthroscopic treatment. A prospective survey-based study

Abstract: The forgotten joint score-12 (FJS-12) may be an advantageous questionnaire in young patients with high hip function and a low level of pain. We investigated the reliability and the responsiveness of the FJS-12 in patients with femoroacetabular impingement undergoing hip arthroscopic treatment. Fifty patients were included in the reliability study and 34 patients were included in the responsiveness study. Test–retest reliability was assessed with intraclass correlation coefficient (ICC), standard error of measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…An a priori power analysis was performed. With an alpha level of 0.05 (two-tailed), minimum power established at 0.80, and a medium effect size of 0.6 (ES, Cohen’s d ) [ 25 ], 24 participants would be necessary to find a statistically significant effect on the model. Data normality for the FJS-12 was assessed using the Kolmogorov-Smirnov test of normality.…”
Section: Methodsmentioning
confidence: 99%
“…An a priori power analysis was performed. With an alpha level of 0.05 (two-tailed), minimum power established at 0.80, and a medium effect size of 0.6 (ES, Cohen’s d ) [ 25 ], 24 participants would be necessary to find a statistically significant effect on the model. Data normality for the FJS-12 was assessed using the Kolmogorov-Smirnov test of normality.…”
Section: Methodsmentioning
confidence: 99%
“…Chahal et al [ 17 ] reported good reliability of PROM for knee joint–specific questionnaires in a test-retest study conducted 6 months after multiligament knee injury. Bramming et al [ 18 ] reported that a PROM (forgotten joint score-12) showed high relative reliability in a test-retest study conducted at 6 months after hip arthroscopic surgery. The differences in follow-ups performed in the first 3 months postsurgery might be due to variability in patient conditions during the acute phase following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The patients’ outcomes were reviewed at a clinically relevant time point, 1 year following surgery. The only comparable data come from a Dutch language study in patients undergoing hip arthroscopy, where an effect size of 0.6 was reported at 6 month follow-up [ 2 ]. A substantially greater effect size of 1.16 was demonstrated at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Bramming et al reported high relative reliability and responsiveness of the FJS-12 in hip arthroscopy using the Dutch translated version of the score in a Dutch population [ 2 ], but this had a comparatively short follow-up period of 6 months. A previous meta-analysis has shown substantial improvements following hip arthroscopy between 6 month and 1 year follow-up [ 8 ], and therefore, this study may not have captured the clinically relevant recovery period and improvement following surgery.…”
Section: Introductionmentioning
confidence: 99%